Bricks in the wall: A review of the issues that affect children of in‐country seasonal migrant workers in the brick kilns of Nepal. Issue 12 (25th September 2020) - Daly, Angela; Hillis, Alice; Shrestha, Shubhendra Man; Shrestha, Babu Kaji
Abstract: This paper explores experiences of Nepalese children of seasonal migrant workers in brick kilns and the particular vulnerabilities they face, as child labourers, as unpaid workers engaging informally in brick production or household work to the support family economy, or as children left behind in poor communities with varying support. The review provides a thematic analysis from child labour and migration literature from Nepal and South Asia from 2010–2020 to explore issues that affect children of families who internally migrate within Nepal to work in brick kilns. Two key themes and eight subthemes consistently emerged across the papers: Seasonal in‐country migration to brick kilns and impacts on children (reasons for children to enter into migrant work; left‐behind children; remittances; the role of gender on work and education) and the situation of children working in Nepalese brick kilns (living conditions; working conditions and occupational ill‐health; psychosocial distress; child protection) . The review found that literature on Nepalese children from brick kiln working families is subsumed into wider studies on migration with impacts on children's lives often reported as outcomes of findings rather than a main focus of studies. Furthermore, there is minimal recent empirical research with such families and children. This may be due to ethical dilemmas of doing research with children and difficulties in maintaining contact with families that move frequently.